Wind Power Integration and Its Impact on Power Quality - A Didactic Approach - Kihwele, Santos (Tanzania Journal of Engineering and Technology, 2021)
This paper presents a model of a wind power system integrated with realistic power system, with intention of using it in addressing power quality issues in relations to grid codes during steady-state operation transient-state operation i.e., presence of grid fault events. For that case, a didactic approach of the normal performance of power systems due to the connection of fixed-speed wind turbine with induction generators is used. A study of integrating wind farms will be presented, including the incidence of high inrush current due to switching capacitor banks, out-rush current and voltage sags due to nearby three phase faults. As mandatory for the grid codes regulation, the incidence on the power quality at the point of common coupling is analyzed too. As a result of the contingency study, it will be shown that capacitors bank and fault current limiter can help the wind farm to ride-through a fault. Keywords: Capacitor bank, fault current limiter, fault ride-through, Grid codes, Inrush current, Out-rush current, Power quality, Voltage sag, Wind farm, and Wind turbine.